2017
DOI: 10.1103/physreve.95.043309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internal mass in the lattice Boltzmann simulation of moving solid bodies by the smoothed-profile method

Abstract: A computational method for the simulation of particulate flows that can efficiently treat the particle-fluid boundary in systems containing many particles was developed based on the smoothed-profile lattice Boltzmann method (SPLBM). In our proposed method, which we call the improved SPLBM (iSPLBM), for an accurate and stable simulation of particulate flows, the hydrodynamic force on a moving solid particle is exactly formulated with consideration of the effect of internal fluid mass. To validate the accuracy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…The results are consistent with those shown in Fig. 17, and good agreement can be found by the simulations of the present IB-DUGKS and iSP-LBM from Yasushi et al [51]. The simulation of a group of circular particles settling in an enclosure is further conducted.…”
Section: A Group Of Particles Settling In An Enclosuresupporting
confidence: 90%
See 1 more Smart Citation
“…The results are consistent with those shown in Fig. 17, and good agreement can be found by the simulations of the present IB-DUGKS and iSP-LBM from Yasushi et al [51]. The simulation of a group of circular particles settling in an enclosure is further conducted.…”
Section: A Group Of Particles Settling In An Enclosuresupporting
confidence: 90%
“…In IBM, the hydrodynamic force coming from the fluid can be simply obtained as a counter-acting force. However, it is found in the previous studies [35,51] that such method only holds for the inertial motion of a body. For the case where the object is accelerated, terms that account for the effect of inertial mass should be added into the force and torque calculation as…”
Section: Particle Dynamicsmentioning
confidence: 99%
“…In the iSP method [24], the effect of particle gravity (F G k ) on the motion of the isodensity fluid flow is implicitly considered in Eq. (2) via the term φ f p , which is given by Eq.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…We recently reported a solid-fluid simulation method based on the smoothed profile (SP) method for the LBM solver [23], which is referred to as the improved SP-LBM (iSP-LBM) [24]. The iSP-LBM improved the accuracy and stability of the original SP-LBM by implementing an exact formulation for the hydrodynamic forces on a moving solid particle with consideration for the effects of internal fluid mass.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mino et al have computed the effect of the internal mass on the particle motion in SPM. Their results have indicated that FiH and TiH introduced in Equations and are not exactly the actual hydrodynamic force and the torque exerted on the i th particle.…”
Section: Numerical Implementationmentioning
confidence: 99%